2017
DOI: 10.1016/j.annepidem.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between smoking and body mass index and risk of oral clefts

Abstract: Purpose To examine maternal smoking and body mass index (BMI) interactions in contributing to risk of oral clefts. Methods We studied 4935 cases and 10,557 controls from 6 population-based studies and estimated a pooled logistic regression of individual-level data, controlling for study fixed effects and individual-level risk factors. Results We found a significant negative smoking-BMI interaction, with cleft risk with smoking generally declining with higher BMI. For all clefts combined, the OR for smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…2 Family history of CL/P in the present study corroborates previous findings of high rates of familial recurrence. 1,32 Brito et al, 32 in a study with 1,042 families from five different locations in Brazil, observed a familial recurrence similar to that observed in the present study, in Barbalha (37%) and in Fortaleza (40%) in the Brazilian state of Ceará. Martelli-Junior et al 33 found that 35.1% of 185 non-syndromic CL/P patients from Minas Gerais, Brazil, had a positive family history of orofacial clefts.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…2 Family history of CL/P in the present study corroborates previous findings of high rates of familial recurrence. 1,32 Brito et al, 32 in a study with 1,042 families from five different locations in Brazil, observed a familial recurrence similar to that observed in the present study, in Barbalha (37%) and in Fortaleza (40%) in the Brazilian state of Ceará. Martelli-Junior et al 33 found that 35.1% of 185 non-syndromic CL/P patients from Minas Gerais, Brazil, had a positive family history of orofacial clefts.…”
Section: Discussionsupporting
confidence: 88%
“…Cleft lip and/or cleft palate (CL/P) is a congenital malformation characterized by the lack of fusion of the upper lip and/or palate, which may be present in isolation or in association with a syndrome. 1 The highest prevalence at birth of CL/P is found in Asian and native American populations (1 in 500 live births), while the lowest prevalence is observed in populations of African descent, with approximately 1 in 2,500 live births. 2 In Brazil, recent studies have indicated that the mean prevalence of CL/P is 5.86 per 10,000 live births, but these rates can vary across different states.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…11,14 Among maternal characteristics confounders, social class, paid work, and schooling represent directly or indirectly on the socioeconomic situation. Maternal smoking, as a confounder, is associated with prematurity, low birth weight and cleft lip, 24,25 characteristics that may be present in the classification of neonatal near miss cases and these are also related to a longer hospitalization. Additionally, smoking itself leads to a higher frequency of neonatal hospitalization, 26 and a higher incidence of pulmonary bronchodysplasia which increases hospitalization length.…”
Section: Discussionmentioning
confidence: 99%
“…Entende-se a fissura labial e/ou palatina como uma malformação caracterizada pela falta de fusão do lábio superior e/ou palato, podendo se apresentar de maneira isolada ou associada a alguma síndrome (Wehby et al, 2017 (Oliveira et al, 2014).…”
Section: Introductionunclassified